The conceptualisation and implementation of the learner-centred approach to TESOL at tertiary level in Vietnam: a case study - Chu, Thi Le Hoang (Curtin University, 2014)
This study investigates teachers’ conceptualisation and implementation of a learner-centred approach to TESOL in Vietnam.The study was conducted as an instrumental single-site case study at an English faculty of a public/national university, involving three data collection methods: questionnaires, interviews and classroom observations.The findings of the study reveal a complex interrelationship amongst teachers’ beliefs and practices and their teaching context, which has important ramifications for TESOL at tertiary level in Vietnam.